A Re-examination of the Holiday Effect in Stock Returns: The Case of Vietnam - Khanh, Pham Dan; Dat, Pham Thanh; Nhuong, Bui Huy (Edelweiss Applied Science and Technology, 2020)
This paper provides empirical evidence of the holiday effect in stock return and the implications of the holiday effect. The research finds that there are existing the high stock return before the Lunar new year on the Ho Chi Minh Stock Exchange during the period 2002-2018. This paper using the GARCH, Modified-GARCH, GARCH-M, and EGARCH models to test the holiday effect on stock return. The results indicate that there is evidence of holiday such as Chinese New Year in Vietnam which is called Lunar new year effect on stock return. Specifically, the stock return before the Lunar new year is usually higher than after the Lunar new year on the Ho Chi Minh Stock Exchange.